Pexidartinib improves physical functioning and stiffness in patients with tenosynovial giant cell tumor: results from the ENLIVEN randomized clinical trial - van de Sande, Michiel; Tap, William D; Gelhorn, Heather L; Ye, Xin; Speck, Rebecca M; Palmerini, Emanuela; Stacchiotti, Silvia; Desai, Jayesh; Wagner, Andrew J; Alcindor, Thierry; Ganjoo, Kristen; Martín-Broto, Javier; et al. (Acta Orthopaedica, 2021)
Background and purpose — The ENLIVEN trial showed that, after 25 weeks, pexidartinib statistically significantly reduced tumor size more than placebo in patients with symptomatic, advanced tenosynovial giant cell tumor (TGCT) for whom surgery was not recommended. Here, we detail the effect of pexidartinib on patient-reported physical function and stiffness in ENLIVEN. Patients and methods — This was a planned analysis of patient-reported outcome data from ENLIVEN, a doubleblinded, randomized phase 3 trial of adults with symptomatic, advanced TGCT treated with pexidartinib or placebo. Physical function was assessed using the Patient-Reported Outcomes Measurement Information System (PROMIS)- physical function (PF), and worst stiffness was assessed using a numerical rating scale (NRS). A mixed model for repeated measures was used to compare changes in PROMIS-PF and worst stiffness NRS scores from baseline to week 25 between treatment groups. Response rates for the PROMIS-PF and worst stiffness NRS at week 25 were calculated based on threshold estimates from reliable change index and anchor-based methods. Results — Between baseline and week 25, greater improvements in physical function and stiffness were experienced by patients receiving pexidartinib than patients receiving placebo (change in PROMIS-PF = 4.1 [95% confidence interval (CI) 1.8–6.3] vs. –0.9 [CI −3.0 to 1.2]; change in worst stiffness NRS = –2.5 [CI −3.0 to −1.9] vs. –0.3 [CI −0.9 to 0.3]). Patients receiving pexidartinib had higher response rates than patients receiving placebo for meaningful improvements in physical function and stiffness. Improvements were sustained after 50 weeks of pexidartinib treatment. Interpretation — Pexidartinib treatment provided sustained, meaningful improvements in physical function and stiffness for patients with symptomatic, advanced TGCT.